KEWAJIBAN PERUSAHAAN DALAM MENJAMIN HAK AMAN PARA PEKERJA: PANDANGAN TENTANG KESELAMATAN DAN KESEHATAN KERJA (K3) - Faizal Dicky Hermansyah (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The company to ensure right workers, including those relating to health and safety work (k3) , an important aspect in maintaining welfare and protection of workers.This study provides perspective on the role and responsibility of the business world in ensuring a safe and healthy work environment to workers.Company has a legal obligation and ethics to provide a safe and healthy work environment, prevent accidents work, and protecting workers health.The pencegahannya covering identification of risk, the application of safety procedures, and training and monitoring stages.Active participation in the implementation of the policy management k3 and ensuring adherence to regulations be key to achieve this aim.Government roles in monitoring and regulating the k3 is also important to make sure the companies to comply with regulations.Synergies between business and government to create ling.